2020
DOI: 10.1002/pol.20200016
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of calcium sulfate whisker using thiol‐ene click reaction and its application in reinforced silicone rubber

Abstract: The hemihydrate calcium sulfate whisker (HCSW) was modified by γ‐(methacryloxy)propyl trimethoxy silane (KH570) and trimethylolpropane tris(3‐mercaptopropionate) via wet modification and thiol‐ene click reaction, and then the unmodified and modified HCSW were added into α, ω‐dihydroxy polysiloxane (DPS) matrix to prepare silicon rubber composites. After the dual‐surface modification, the surface of HCSW was transformed to hydrophobic, the hydration of whisker was obviously improved, and the whisker dispersed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…[25][26][27] Because of the small size and large strength of calcium sulfate whisker can play a skeleton role when added to polymer materials, and the mechanical properties of CSW often significantly improve. [28][29][30] At the same time, calcium sulfate whiskers have good compatibility and good interface binding strength, the advantages of ultra-fine inorganic filler and enhanced fiber can be used as efficient functional materials, based on non-toxic characteristics as additives added to PP will not aggravate the harm caused by white pollution. [31][32][33] Previous studies have demonstrated that the use of nano-TiO 2 as a filler significantly impacts the aging performance of PP products.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Because of the small size and large strength of calcium sulfate whisker can play a skeleton role when added to polymer materials, and the mechanical properties of CSW often significantly improve. [28][29][30] At the same time, calcium sulfate whiskers have good compatibility and good interface binding strength, the advantages of ultra-fine inorganic filler and enhanced fiber can be used as efficient functional materials, based on non-toxic characteristics as additives added to PP will not aggravate the harm caused by white pollution. [31][32][33] Previous studies have demonstrated that the use of nano-TiO 2 as a filler significantly impacts the aging performance of PP products.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrothiolation reaction for surface modification finds use in the production of new composite materials for catalysis, chromatography [ 153 ], including the capillary columns for enantioselective nano-HPLC [ 154 , 155 ], for improving the strength characteristics of rubbers [ 156 ], and for biomedical purposes in the immobilization of enzymes such as chemotrypsin [ 157 ] and acetyl cholinesterase [ 158 ].…”
Section: Introductionmentioning
confidence: 99%